The rare entity of bilateral and unilateral neuroendocrine metastases to the breast: a case series and literature review - Zagami, Paola (Ecancermedicalscience, 2020)
INTRODUCTION: Primary neuroendocrine neoplasms (NENs) in the breast are very rare. Until 2011, the prevalence was 0.1% of all breast lesions and 1% of all NENs, whereas metastatic breast NENs represent 1%–2% of all breast tumours. However, it seems that over the last 5 years the diagnostic frequency of breast NENs has increased, probably for more alert specialists and advanced diagnostic tools, leading to a prevalence of 2%–5% of diagnosed breast cancers, mostly in the elderly population. Breast metastases from extramammary malignancies are uncommon and bilateral ones are even more uncommon, with few reported in the literature. We describe four clinical settings of breast metastases from different NENs and the multidisciplinary approach for diagnosis and treatment. METHODS: Four patients were found to have NEN primaries metastasised to the breast. A literature review was conducted to identify similar cases and characterise breast metastases from neuroendocrinal tumors (NETs). RESULTS: Two patients presented with bilateral breast metastases (one with well-differentiated panNET and another with atypical lung carcinoid) and two had unilateral (one with moderately differentiated lung NET and one with atypical lung carcinoid). There are about 13 cases of NEN breast metastases reported in the English literature. The ileum is the most common primary site, followed by the appendix, duodenum, pancreas and lung. CONCLUSION: Breast lesions from extramammary primary often pose a diagnostic challenge, since a breast nodule can be the first and often the only presentation of the disease. However, differentiating between primary and secondary NEN breast lesions is essential, owing to different clinical management and prognosis.